Spectroscopic examination and release of microencapsulated oregano essential oil - Ioannis Partheniadis; Panagiota Karakasidou; Souzan Vergkizi; Ioannis Nikolakakis (International Association of Physical Chemists (IAPC), 2017)
Oregano essential oil (EO) of Greek origin with high carvacrol content (86.84 %) was encapsulated by spray drying using Arabic gum, modified starch and maltodextrin (75:12.5:12.5) as wall materials. The spray-dried product (EOSD) consisted of roundish particles with narrow size distribution. FT-IR and Raman spectroscopy identified the EO in EOSD, with Raman spectra showing more distinct peaks and a small shift of the peak at 1260 cm-1 (assigned to the stretching vibration of the bond of C-O of the phenol), implying only minor chemical interaction with the wall materials. Release of the EO from EOSD was described by the Hixson-Crowell equation (R2=0.986) with apparent diffusion coefficient 8.3x10-10 m2/s. These findings indicate that microencapsulation by spray drying did not affect the quality of the oregano EO and provided relatively fast and complete release.